UNDERSTANDING IDENTITY CONSTRUCTION OF INDONESIAN EFL TEACHER EDUCATORS FROM A THREE-DIMENSIONAL NARRATIVE - Ubaidillah, M. Faruq; Andriyanti, Erna; Triastuti, Anita (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2024)
Research into language teacher identity construction has proliferated in recent years. However, studies examining identity construction from an integral perspective of EFL teacher educators’ past, present, and future narratives seem sparse. To fill this lacuna, the present study was designed to explore five Indonesian EFL teacher educators’ identity construction from their past, present, and future narratives. This study’s data were generated through multiple life-historical interviews with the five participants. The thematic analysis showcased that language teacher identity is constructed as a continuum from the teachers’ past experiences as EFL learners, present experiences as lecturers and doctoral students, and future narratives as imagined teacher educators. The findings also revealed that the participating teachers constructed their language teacher identity through complex and context-dependent experiences in their past, present, and future narratives. Based on the study’s findings, we offer a novel approach to studying language teacher identity construction employing teachers’ three-dimensional narratives. This approach enables teachers to understand themselves and their relationships with social environments through the interconnectivity of their past, present, and future narratives.